Solvent Dependence of the Electronic Absorption Spectra of Mercury-Phthalocyanine - SRIVASTAVA, K.P.; KUMAR, A. (Asian Journal of Chemistry, 2010)
The electronic absorption spectra of Hg-phthalocyanine have been recorded with a view to study the solvent solute interaction, H-bonding effect and protonation of Hg-phthalocyanine in sulphuric acid of different strengths and other polar solvents. The study revealed that Hg-phthalocyanine acts as a monoacidic base in aqueous acidic medium. The spectra contained two electronic bands, which are assigned as Q-band and Soret band, which are attributed to the allowed a1u→2eg and a2u&rarr2eg transitions respectively. The bathochromic shift of λmax was observed which is due to the H-bonding effect of the polar solvents.